VISUALISASI MESIN HASRAT PADA IKLAN OLATTE MELALUI PENDEKATAN SEMIOTIKA - Akmal Pijar Aradhana; Guruh Ramdani; Nathaniela Anya Jeconia Manoppo; Muhammad Fadlhy Fajarsyach; Jinanti Audiza; Muhamad Aditya Nursyahbani (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
This study is motivated by the importance of understanding the role of visual elements in building consumer desire through advertisements, particularly in the case of Olatte pear-flavored beverage. In a consumerist society, desire does not arise naturally but is constructed through media and visual symbols. This research employs a descriptive qualitative method with Charles Sanders Peirce's semiotic approach, combined with literature study as the data collection technique. The findings reveal that visual elements in the Olatte advertisement—such as water, chili, and pear—function as icons, indexes, and symbols that construct meaning and stimulate consumers' desire to purchase the product. The advertisement strategically employs the concept of the "desiring-machine" by Deleuze and Guattari to generate emotional appeal. Advertisements, therefore, are not merely informative tools but also serve to shape perception and consumer needs. The implication of this study highlights the powerful influence advertisements have on shaping public perception and consumer behavior, underscoring the importance of critical awareness among audiences when engaging with visual messages in everyday life.